(untitled) (Proceedings of International Conference on Special Education, 2015)
The teaching and learning system for special education in Malaysia is being enhanced using ICT, specifically through the incorporation of edutainment elements. This is part of the education policy launched in year 2010, which emphasises the importance of inclusive education system. This paper presents the findings of a preliminary study for e-project based learning (eProjBL) in special education conducted in an urban primary school equipped with a computer lab. A total of twelve students consisting of six students with special needs and six prime students were involved in a one week experiment along with their two teachers. An eProjBL module was designed with features such as augmented reality, virtual reality, computer-based games, animation projects and other edutainment elements. The testing session was designed to explore students’ and teachers’ acceptance of the eProjBL module in special education. The observation was done through teacher evaluation via rubric, engagement form, post question for both teachers and students, spontaneous informal conversations and observations. The preliminary findings provide areas for further refinement of the eProjBL strategies for special education